Penerapan Metode Analytical Hierarcy Process (AHP) Untuk Menentukan Bidan Teladan - Purnomo, Wulan Andang (RC-INSTITUT, 2018)
Improving the quality of midwifery services is one of the most crucial issues in the field of health services, so that the need for improvement and improvement of human resources for the creation of excellent health services. Puskesmas Tiumang requires skilled and professional midwives to provide health services to the community, and this is a role model for determining exemplary midwives. So far, the work area of ​​Puskesmas Tiumang does not have a screening and assessment system to determine the exemplary midwife. This study aims to apply the method of Analytical Hierarcy Process (AHP) in determining exemplary midwives in the work area of ​​Puskesmas Tiumang of Dharmasraya Regency. The framework in this research is; (1) data collection; (2) system analysis; (3) system design; (4) implementation and testing, and; (5) system evaluation. Based on the results of the analysis using Analytical Hierarcy Process (AHP) method, the ranking of exemplary midwives in the work area of ​​Tiumang Health Center. The results of this study can be used as a decision support tool in determining exemplary midwives in the work area of ​Puskesmas ​Tiumang Dharmasraya District. Keywords: Decision Support System, Analytical Hierarcy Process (AHP), Exemplary Midwife.